PENGARUH PROFITABILITAS DAN UKURAN PERUSAHAAN TERHADAP PENGUNGKAPAN TANGGUNGJAWAB SOSIAL PADA PERUSAHAN ASURANSI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Amrina Rosyada; Fenty Astrina (Department of Accounting, Faculty of Economics, Universitas Sriwijaya, 2018)
The purpose of this study is to analyze the effect of profitability and firm size on the disclosure of social responsibility on insurance companies as independent variables using profitability and firm size variables on social responsibility disclosure (CSR) as the dependent variable in company annual report, Respectively) and simultaneously (together). The sample that is the object of this research is all insurance companies listed on the Indonesia Stock Exchange in 2013 to 2016, the total sample for research four years of observation is 40 samples by using purposive sampling. The data used are secondary data from annual reports and performance reports of insurance companies that have been published. The data analysis technique used is multiple linear regression with the help of SPSS version 22. The results of this study are as follows, 1. Profitabilias Insurance company has a negative and insignificant effect on corporate CSR, 2. The size of the Insurance Company has a negative and significant effect on CSR. The results of this study provide information for companies about the level of disclosure of social responsibility owned by insurance companies, and also useful for providing information for decision making.